2018
DOI: 10.1111/jar.12495
|View full text |Cite
|
Sign up to set email alerts
|

“I don't want to take any risks even if it's gonna mean this service‐user is gonna be happier”: A thematic analysis of community support staff perspectives on delivering Transforming Care

Abstract: Recommendations are provided for how staff perspectives should inform Transforming Care in interests of service-users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Clifford et al. (2018) note that the ability to balance safety and quality of life needs was a barrier to guideline implementation. The current research supports this, as often staff were well‐intending, however, reverted to a harm minimization approach when faced with conflicting demands.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clifford et al. (2018) note that the ability to balance safety and quality of life needs was a barrier to guideline implementation. The current research supports this, as often staff were well‐intending, however, reverted to a harm minimization approach when faced with conflicting demands.…”
Section: Discussionmentioning
confidence: 99%
“…Research has suggested that staff‐related barriers to implementation are sometimes driven by staff perceptions and concerns. Risk management research has illustrated that staff are concerned about the therapeutic relationship within risk management (Downes et al., 2016), a lack of guidance, support (Reddington, 2017), and the ability to balance safety and quality‐of‐life needs (Clifford et al., 2018). Downes et al (2016) found that mental health nurses believed that while risk assessment could aid professional decision‐making, some expressed concerns that the process could be dehumanizing, while others did not agree with the role of positive risk taking within recovery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Questions on the interview schedule were open, and technical language was avoided to minimise confusion (Smith & Osborn, 2015). Questions were designed following consultation of the issues related to TC obtained via systematic review of literature such as that written by Taylor et al, (2017) and Clifford et al, (2018).…”
Section: Alternative Non-nursing Profession Such As Occupational Therapymentioning
confidence: 99%
“…Failure to do so leads to feelings of oppression, powerlessness, stress and exhaustion (Quilliam et al , 2018). Clifford et al (2018) identified that collaborative risk taking and decision-making is likely to empower staff to use more values based and less restrictive strategies which is encouraged across legislation (DH, 2014; HCHL, 2019).…”
Section: Introductionmentioning
confidence: 99%